Нарушения хронотропной функции сердца при послеоперационном гипотиреозе в эксперименте - Михайличенко, В.Ю.; Василянская, О.В.; Коноплянко, В.А.; Коноплянко, Т.А.; Штода, Д.Е.; Веселый, В.Я. (Таврический медико-биологический вестник, 2013)
У статті автори описують порушення хронотропної функції серця при післяопераційному гіпотиреозі. Відзначається значне зниження базової частоти серцевих скорочень у щурів, при стрес-імітуючого навантаженню катехоламінами з’являються аритмії, явища ішемії міокарда й нездатністю серця розвити достатню частоту скорочення для адекватної відповіді. The heart rate number in rest of rats with postoperational hypothyroidism is significantly decreased, the stress-simulating load leads to the ischemic phenomenon in the myocard, heart rhythm abnormalities and significantly low response of heart muscle versus the intact animals. So, metabolic abnormalities in the myocard in hypothyroidism lead to the dystrophic changes in myocard that is precisely reflected in the activity abnormality of cardiovascular system.